Vulnerability to Food Insecurity in a Telecoupled World: Insights From Vanuatu - Nef, Danny Philipp; Kotra, Krishna Kumar; Stauffacher, Michael; Six, Johan; Kruetli, Pius (Frontiers in Sustainable Food Systems, 2022)
Food insecurity is a pressing problem in many regions across the world. Drivers of food insecurity are becoming increasingly embedded in sociocultural and economic processes that transcendent multiple spatial and temporal scales. This is due to the increasingly globalized interconnections of places and people. Understanding this complexity is essential to devise locally relevant and effective adaptation strategies to tackle existing vulnerabilities causing food insecurity. This article analytically addresses the complexity in cross-scale dynamics by combining a case study from northern Vanuatu with a conceptual analysis of the broader socioeconomic dynamics within the telecoupling framework. Our aim is to identify drivers of vulnerability that span multiple temporal and spatial scales and contribute to food insecurity in a given location while exploring the relevance and applicability of the framework for the holistic assessment of vulnerability to food insecurity. The transdisciplinary approach used in this work involved local community members and local agriculture extension officers at all stages of the study process. For this, we used complementary research methods, such as workshops, participant observations, and in-depth interviews. The results showed that potential vulnerability to food insecurity in northern Vanuatu is likely to be related to individual choices aimed at maximizing income, enabled by economic development and driven by socio-cultural changes. These choices and their consequences are perceived in many cases to be responsible for lower subsistence food production and the overuse of natural food resources. However, economic changes in particular can also enable additional livelihoods that complement existing (subsistence-based) strategies, leading to a reduction in one-sided dependencies and thus to an overall increase in the resilience of local livelihoods. We find the telecoupling approach to be a useful tool to holistically capture a local vulnerability context. However, we also encountered challenges in describing telecouplings that operate over longer time scales.